«MANUAL» REGULATION OF PRICES FOR MILITARY GOODS: SPECIAL FEATURES AND MECHANISMS OF PROMPT REDUCTION - А. M. Moskovsky (Стратегические решения и риск-менеджмент, 2014)
Special features of military goods pricing are considered here within the state arms program and defence order. A number of research guidelines are stated here for the purpose of solving problems in this area.